Relasi Islam Dengan Tradisi Larung Sesaji Gunung Kelud Di Kabupaten Kediri - Rahmattus S., Tania; Laila A, Najwa; Taqbirotul F. A., Nabilla; Chabibatur R., Risma; Aji P. Jf., Pandu; Muhammad Noor, Aditia (Postmodernism: Indonesian Journal of Multidisciplinary Islamic Studies, 2025)
Culture has a strong relationship with Islam. Likewise what happened in Kediri Regency, where Islam and local culture in Kediri Regency have a strong relationship as well. Larung Sesaji is being the traditional ceremonies held by the people of Kediri Regency. This article was created to find out how Islamic relations were formed through the culture of throwing offerings at Mount Kelud in Kediri Regency and to find out how the existence of Islam and the culture of throwing offerings in the Muslim community of Kediri Regency. This research is intended to find out the Islamic relations that were formed through the tradition of throwing offerings at Mount Kelud in Kediri Regency and to find out how the existence of Islam and the culture of throwing offerings in the Muslim community of Kediri Regency. The research method used is in the form of description, interpretation and understanding of a phenomenon/ experience which is carried out through observation of qualitative data and is non-numeric in nature. In addition, using the Library Research method which utilizes data from several literatures. From the research it was found that in Kediri Regency, the existence of the community was proven through the tradition of Mount Kelud's Larung Saji. The procession of the symbolic ritual offerings has da'wah values ​​that develop culturally, which can be proven through history which states that Islam itself is embedded in society through cultural diversity. The tradition of serving food is also an intermediate as well as an "event" for cross-community groups to establish friendships. Harmony in the dynamics of life contributes to building an advanced civilization in society.